Predicting Links from Education Network of Employees - Kocaman, Ceyda; Orman, Gunce Keziban (Lecture notes in engineering and computer science, 2023)
The advances in technology and data science affect many fields positively. One of these fields is education. Learning analytics have the potential to develop new ways of achieving excellence in teaching and learning. The companies try to use learning analytics techniques for their employees' education and aim to improve employee performance. The education data sets of Softtech employees are used in this study. Softtech is a software company in Turkey, and those data sets include different types of technical, non-technical, online, and offline education. All data sets are combined, and an employee network is created by connecting employees via education. In this study, complex network analysis, link prediction, and machine learning techniques are applied with the aim of creating an education recommendation system.